Rheumatoid arthritis, its prevalence and incidence in different countries - A. O. Plakhova; V. N. Sorotskaya; D. Sh. Vaisman; R. M. Vaisman (Современная ревматология, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that manifests itself not only in progressive destruction of joints, but also in systemic damage to internal organs, which leads, despite significant success in therapy, to a decrease in the quality of life of patients, temporary or permanent loss of ability to work. Data on the prevalence of RA and its incidence in different countries are presented, the influence of various factors on these indicators is discussed.